PENERAPAN MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVICIONS) BERBANTUAN MEDIA KOMIK POLAMATIKA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI SMP NEGERI 4 JEMBER - Wayuda, Irma Amelinda; Suharto, Suharto; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2017)
Abstract.Mathematics learning with cooperative model using STAD type is learning technique which focused on the development of student social skill in the learning activity with teamwork, STAD composed from five stages there is learning material, teamwork, quiz or test, individual score and reward. Comic Learning is a media which can using for anticipate problem when student learn subject material. Role of polamatics in arithmatics comic is for helping student doing multiplication count quick and precise. This research has purpose to reviewing applications STAD assisted comic polamatics otherwise to improve activity and student learning result at VII-C classroom, 04 Jember Junior High School . Reasearch type which was used in this research is qualitative descriptive type, Collecting data method has been using in this research is interview and observation. Research instrument using RPP, Comic Polamatics Media, teacher & student observation sheet and question sheet I and II cycle. Based on research result application STAD assisted comic polamatics increasing activity teacher and student learning result during learning process. Teacher activity increased by 14,41 % while student activity increased by 15,625 % and student learning result increased by 16,78 %. Keywords: STAD, Comic polamatica, learning result